2022
DOI: 10.3390/life12121990
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events of PD-1 or PD-L1 Inhibitors in Triple-Negative Breast Cancer: A Systematic Review and Meta-Analysis

Abstract: (1) Background: This study aimed to develop a comprehensive understanding of the treatment-related adverse events when using PD-1 or PD-L1 inhibitors in triple-negative breast cancer (TNBC). (2) Methods: We conducted a meta-analysis of Phase II/III randomized clinical trials. Studies were searched for using PubMed, Embase, and Cochrane Library from 1 March 1980 till 30 June 2022. Data on adverse events were mainly extracted from ClinicalTrials.gov and published articles. A generalized linear mixed model with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
(68 reference statements)
0
7
0
1
Order By: Relevance
“…In another meta‐analysis, the risk of pneumonitis was significantly increased with anti‐PD‐1/PD‐L1 therapies in TNBC (odds ratio: 2.52; 95% CI: 1.02–6.26) 33 . The reasons for the higher rates of pneumonitis in this study are unknown, but it is generally agreed that this immune‐related AE is tumor‐specific, 31,32 occurring due to the immunosuppressive effects of the anti‐PD‐(L)1 drug combination 33 ; nevertheless, underlying reasons for this warrant further research. Notwithstanding the rates of pneumonitis, mivavotinib in combination with nivolumab appeared to have a generally manageable safety and tolerability profile.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In another meta‐analysis, the risk of pneumonitis was significantly increased with anti‐PD‐1/PD‐L1 therapies in TNBC (odds ratio: 2.52; 95% CI: 1.02–6.26) 33 . The reasons for the higher rates of pneumonitis in this study are unknown, but it is generally agreed that this immune‐related AE is tumor‐specific, 31,32 occurring due to the immunosuppressive effects of the anti‐PD‐(L)1 drug combination 33 ; nevertheless, underlying reasons for this warrant further research. Notwithstanding the rates of pneumonitis, mivavotinib in combination with nivolumab appeared to have a generally manageable safety and tolerability profile.…”
Section: Discussionmentioning
confidence: 98%
“…Two meta‐analyses of previous studies have reported rates of ~1% for grade ≥3 pneumonitis with anti‐PD‐1 monotherapy across cancer types, with only slightly increased rates for combination therapy 31,32 . In another meta‐analysis, the risk of pneumonitis was significantly increased with anti‐PD‐1/PD‐L1 therapies in TNBC (odds ratio: 2.52; 95% CI: 1.02–6.26) 33 . The reasons for the higher rates of pneumonitis in this study are unknown, but it is generally agreed that this immune‐related AE is tumor‐specific, 31,32 occurring due to the immunosuppressive effects of the anti‐PD‐(L)1 drug combination 33 ; nevertheless, underlying reasons for this warrant further research.…”
Section: Discussionmentioning
confidence: 99%
“…The United States Food and Drug Administration (FDA) granted approval in the year 2019 for the utilization of the PD-L1 inhibitor (Atezolizumab) in conjunction with chemotherapy (Abraxane) as a treatment for patients with metastatic TNBC [45]. Later, numerous cancer studies have been involved in using ICIs as alternative cancer therapy, particularly in triple-negative breast cancer.…”
Section: Monotherapy-icismentioning
confidence: 99%
“…IrAEs können prinzipiell jedes Organsystem betreffen und sich in unterschiedlichster Form zeigen. Das Spektrum der Nebenwirkungen ist homogen, die Häufigkeit der Toxizitäten variiert jedoch abhängig von Substanz und Dosis des gewählten ICIs sowie der Art des Malignoms und reicht von 45–96 % [ 4 7 ]. Im Generellen sind Rate und Schweregrad an irAEs unter CTLA4-Inhibitoren größer als unter PD-1/PD-L1-Inhibitoren, wobei PD-L1-Inhibitoren etwas besser verträglich zu sein scheinen als PD-1-Inhibitoren [ 2 , 5 ].…”
Section: Epidemiologieunclassified